Effect of Bed Preparation on Native Wildflower Establishment, Weed Control, and Arthropod Presence - Joseph S. Shelton; Svoboda V. Pennisi; Mark Czarnota (Horticulturae, 2023)
Native flowering forbs plantings have been found to support diverse arthropod communities by providing year-round forage and refuge from prey and chemical pollutants. Typically, pollinator habitats are planted from seeds; however, poor establishment and weed pressure often result in limited success of the planting. In this study, we evaluated two bed preparation techniques, a glyphosate treatment with no tillage and tillage with soil fumigant (dazomet) to determine their impact on herbaceous perennial transplants establishment, weed control, and arthropod presence. Our results suggest that forbs grown in beds that are tilled and treated with dazomet exhibit greater growth, produce more blooms, and experience reduced weed pressure compared to plants grown in untilled beds treated with glyphosate. We also found that the bed preparation method had no effect on arthropod activity, despite higher bloom counts in plants grown in beds prepared with tillage and dazomet applications. This research indicates that of the fifteen native flowering forbs examined in this study, a majority attracted abundant and diverse insect populations, despite variations in plant growth and bloom counts due to bed preparation treatments.